2006
DOI: 10.1128/aem.02612-05
|View full text |Cite
|
Sign up to set email alerts
|

Shifting the pH Profile of Aspergillus niger PhyA Phytase To Match the Stomach pH Enhances Its Effectiveness as an Animal Feed Additive

Abstract: Environmental pollution by phosphorus from animal waste is a major problem in agriculture because simple-stomached animals, such as swine, poultry, and fish, cannot digest phosphorus (as phytate) present in plant feeds. To alleviate this problem, a phytase from Aspergillus niger PhyA is widely used as a feed additive to hydrolyze phytate-phosphorus. However, it has the lowest relative activity at the pH of the stomach (3.5), where the hydrolysis occurs. Our objective was to shift the pH optima of PhyA to match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 42 publications
2
67
1
4
Order By: Relevance
“…Our results are in agreement with the results obtained by Tsang et al [9]. Differences in the activity and amount of other enzymes connected with low and very low pH were found by different authors [9,[23][24][25]. Long-term effect of heavy metal ions, low pH and changes in the gene expression were represented on the morphological characteristics of hyphae and heads carrying spores (Fig.…”
Section: Resultssupporting
confidence: 93%
“…Our results are in agreement with the results obtained by Tsang et al [9]. Differences in the activity and amount of other enzymes connected with low and very low pH were found by different authors [9,[23][24][25]. Long-term effect of heavy metal ions, low pH and changes in the gene expression were represented on the morphological characteristics of hyphae and heads carrying spores (Fig.…”
Section: Resultssupporting
confidence: 93%
“…Recently phyA was site-mutated to phyA m and phyCs was synthesized without altering the protein sequence of phyC according to the Pichia pastoris codon usage bias because of the low productions of wild-type phyA and phyC phytases in P. pastoris, and we overexpressed them in yeast as an active and extracellular enzyme (Chen et al, 2005;Zou et al, 2006). The phyA (phyA m ) phytase exhibits an optimum pH at 2.5 to 5.5, having a pH-activity profile ideally suited for maximal activity at low pH point (Chen et al, 2003;Kim et al, 2006). The phyC (phyCs) phytase exhibits an optimum pH around 6 to 9, suitable for neutral tracts and is more thermostable (Janne et al, 1998;Kim et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Both of these enzymes not only share a common catalytic mechanism, but they also display considerable amino acids divergence in their molecular structure. Previous studies have shown that a change of just a single amino acid can alter physical properties of these enzymes [7,8]. In addition, researchers have shown that significant differences exist in these two enzymes in their response to sodium chloride [9].…”
Section: Discussionmentioning
confidence: 99%